2021
DOI: 10.18393/ejss.972062
|View full text |Cite
|
Sign up to set email alerts
|

Hygienization assessment during heap co-composting of Turkey manure and olive mill pomace

Abstract: Article InfoThis study aimed to investigate the co-composting time effectiveness as well as the effect of the initial Carbon/Nitrogen ratio (C/N)i variation on the hygienization of olive pomace and turkey manure. Six different heaps, at 3 levels of (C/N)i ratios: 20, 22 and 28, were installed and monitored during 6 months and assessed at three steps: At the beginning, the end of thermophilicphase and the end of curing-phase. The microbial monitoring concerned 5 microbial pathogens contents, used as hygiene mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…On the other hand, agricultural livestock and agri-food intensification produce large quantities of organic wastes which can lead to environmental pollution and compromise the sustainability of agricultural production [11,22]. Furthermore, organic waste, whether animal or plant matter, is a potential source of organic matter and plant nutrients [3,6]. Moroccan biowaste has been estimated by El-mrini et al [23] at 34.7 million tons a year, while Azim et al [11] have concluded that there is a potential for organic waste estimated up to 1 million tons of dry matter a year, and 13 million euros worth of N, P, and K that can be recovered from the horticultural wastes, only in the Souss Massa region in the south of Morocco.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, agricultural livestock and agri-food intensification produce large quantities of organic wastes which can lead to environmental pollution and compromise the sustainability of agricultural production [11,22]. Furthermore, organic waste, whether animal or plant matter, is a potential source of organic matter and plant nutrients [3,6]. Moroccan biowaste has been estimated by El-mrini et al [23] at 34.7 million tons a year, while Azim et al [11] have concluded that there is a potential for organic waste estimated up to 1 million tons of dry matter a year, and 13 million euros worth of N, P, and K that can be recovered from the horticultural wastes, only in the Souss Massa region in the south of Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…Turkey livestock activities had significantly increased in Morocco, which led to a rise in turkey manure generation. Turkey manure composting is a suitable technology able to recycle nutrients, prevent greenhouse gas emissions, and supply nutrients that can improve soil fertility and enhance crop yields [3,32,55]. Another sector that constitutes a source of potential pollution is olive oil production, which has experienced an important development following the implementation of the Green Morocco Plan in 2008 [12].…”
Section: Introductionmentioning
confidence: 99%